Assessment of Recovery and Resilience Livelihoods after Earthquake in Gorkha District, Gandaki Province, Nepal - N.B. Thapa (Lowland Technology International, 2020)
The study aims to assess the recovery and resilient livelihoods in the earthquake affected population of Gorkha district. The participatory learning and action methods were adopted while conducted the field study. The large majority of the respondents (92 %) have rated happy with the program. The overall changes have found from 1.4 to 08, 4.25 to 8.25 and 0.66 to 5.3 mean score out of ten in shelter, WASH and livelihoods recovery components respectively during before and after situation mapping of earthquake affected survivors. This is considered as significant contribution of recovery and resilient livelihoods program to make a difference in the life of earthquake affected survivors in Gorkha district. There have been completed around 79.76 per cent private houses until the end of September 2019 in Gorkha district whereas only 45.24 per cent private houses have been reconstructed in the overall highly affected areas (14 districts) of Nepal. In the study areas, the participation of women in the humanitarian support process has increased particularly in decision-making process at households, community and Rural Municipality level. There has been increased women participation in development works and division of work between women and men. There has been increased demand by local representatives to increase linkage and coordination with municipalities from the very beginning.